The NIMA-related kinase family and cancer - Li, Haotian; Li, Junhan; Zhang, Yue; Cao, Ran; Guo, Congcong; Jiao, Mingwen (Frontiers in Oncology, 2025)
Cancer is a disease where cells begin to divide uncontrollably and spread to other parts of the body. Mitotic kinases play a crucial role in the initiation and progression of all human malignancies, making them common therapeutic targets. However, a significant portion of the human kinome has yet to be functionally studied in cancer systems. The NIMA-related kinase family (NEKs), consisting of 11 members distributed across different cellular regions, are important protein kinases that regulate mitotic processes. Emerging research suggests that NEK family members have potential key roles in various malignancies. This review systematically summarizes the expression and regulatory mechanisms of NEK family members in different cancer systems, highlighting that targeting NEKs holds promise as a new therapeutic approach for inhibiting cancer growth and metastasis.